(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2013)
For more than half a century, the African-based Rastafarian movement has existed and thrived. Since the early 1930s, Rastafari has developed, changed and gained enough supporters to be considered “one of the most popular Afro-Caribbean religions of the late twentieth century. According to a survey conducted in 1997, there are over one million practicing Rastafarians worldwide as well as over two million sympathizers. Rastafarians are concentrated in the Caribbean, though members of this diverse movement have settled in significant numbers all throughout the world. At present, there are large Rastafarian communities in New York, Miami, Washington DC, Philadelphia, Chicago, Huston, Los Angeles, San Francisco, Boston and New Haven as well as many large cities in Canada, Europe, South America and Africa. While Rastafari has maintained much of its original flavour, migration, globalization and a reinterpretation of philosophical dogma has created a space for white people to join this typically black movement.